Respuesta :

Answer:

x = 12

Step-by-step explanation:

Solve for x:

[tex] \longrightarrow [/tex] 5 (x - 6) = 2(x + 3)

Expand out terms of the left hand side:

[tex] \longrightarrow [/tex] 5x - 30 = 2(x + 3)

Expand out terms of the right hand side:

[tex] \longrightarrow [/tex] 5x - 30 = 2x + 6

Subtract 2x from both sides:

[tex] \longrightarrow [/tex] (5x - 2x) - 30 = (2x - 2x) + 6

5x - 2x = 3x:

[tex] \longrightarrow [/tex] 3x - 30 = (2x - 2x) + 6

2x - 2x = 0:

[tex] \longrightarrow [/tex] 3x - 30 = 6

Add 30 to both sides:

[tex] \longrightarrow [/tex] 3x + (30 - 30) = 30 + 6

30 - 30 = 0:

[tex] \longrightarrow [/tex] 3x = 6 + 30

6 + 30 = 36:

[tex] \longrightarrow [/tex] 3x = 36

Divide both sides of 3x = 36 by 3:

[tex] \longrightarrow [/tex] [tex] \sf \dfrac{3}{3}x = \dfrac{36}{3} [/tex]

[tex] \sf \dfrac{3}{3} = 1: [/tex]

[tex] \longrightarrow [/tex] [tex] \sf x = \dfrac{36}{3} [/tex]

[tex] \sf \dfrac{36}{3} = 12: [/tex]

[tex] \longrightarrow [/tex] x = 12

Answer: 12

Step-by-step explanation: On Edge!!!!!!!!!!!!!!!!!!!